Synthesis and characterization of noble metal/metal oxide nanoparticles and their potential antidiabetic effect on biochemical parameters and wound healing - Elobeid Mai A.; Awad Manal A.; Virk Promy; Ortashi Khalid M.; Merghani Nada M.; Asiri Atheer M.; Bashir Emadeldin Abdeljabar Ali (Green Processing and Synthesis, 2022)
The study assessed the antidiabetic effect of Solenostemma argel and its nanoformulations with silver/gold nanocomposites (CNPs), zinc oxide nanoparticles (ZnONPs), and metaformin drug. Experimental groups consisted of normal control, diabetic control, and four diabetic groups treated with metformin, CNPs, ZnONPs, and bulk argel leaf extract (So-argel). Transmission electron microscopy characterization showed that the synthesized CNPs and ZnONPs were of variable sizes and dimensions and were quasi-spherical in shape. Particle sizes measured by dynamic light scattering were 106 and 139 nm for CNPs and ZnONPs, respectively. Also, the polydispersity index values were 0.473 and 0.269 for CNPs and ZnONPs, respectively. The biochemical parameters were as follows: the group treated with bulk So-argel (105.00 ± 4.041 mg·dL−1) and CNPs (109.00 ± 8.373 mg·dL−1) showed a more profound anti-hyperglycemic effect and were comparable to the control (88.40 ± 2.249). Liver and kidney functions (p ≤ 0.05) improved with So-argel and its nanoformulations compared to metformin. However, bulk argel (170.33 ± 20.431  and 38.00 ± 3.05 U·L−1) and the nanocomposite (228.33 ± 11.464 and 48.00 ± 5.291 U·L−1) were efficacious in lowering serum levels of liver enzymes (AST and ALT, respectively). No significant difference was observed between urea levels. Nevertheless, bulk So-argel (0.26 ± 0.007) and CNPs (0.24 ± 0.018) were more effective than ZnONPs (0.41 ± 0.289) on serum creatinine. Nanotreatment exhibited a reduction in lesions size/healing. Overall, nanoparticles may offer a safe potential for Type 2 diabetes management.